Dampak Budaya Organisasi dan Komitmen Afektif terhadap Retensi Karyawan Generasi Z di Industri Kreatif - Poltak Evencus Hutajulu (Trending: Jurnal Manajemen dan Ekonomi, 2026)
Changes in the workforce composition, now dominated by Generation Z, present new challenges for organizations, particularly in retaining employees in the highly dynamic and talent-driven creative industry. This generation is known for its unique characteristics, such as a tendency toward high job mobility, a need for a flexible work environment, and an orientation toward meaning and emotional attachment in their work. This study aims to analyze the influence of organizational culture and affective commitment on Generation Z employee retention, as well as to test the role of affective commitment as a mediating variable in this relationship. This study employs a quantitative approach with an explanatory design. Data were collected via a questionnaire distributed to 120 respondents who are Generation Z employees in the creative industry sector. Data analysis was conducted using multiple linear regression and mediation tests to identify direct and indirect relationships among the variables. The results indicate that organizational culture and affective commitment have a positive and significant effect on employee retention. Furthermore, affective commitment was found to act as a mediating variable that strengthens the influence of organizational culture on retention. These findings indicate that a supportive work environment not only has a direct impact on employees’ desire to stay, but also enhances emotional attachment, which ultimately strengthens employee loyalty. This study suggests that strategies for retaining Generation Z employees should not focus solely on structural aspects of the organization but must also consider psychological dimensions, particularly in building emotional bonds between employees and the organization. Thus, developing an adaptive and humanistic organizational culture is key to improving employee retention in the creative industry.